2014
DOI: 10.1152/jn.00851.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amplitude correlations on coherence in the local field potential

Abstract: Neural activity across the brain shows both spatial and temporal correlations at multiple scales, and understanding these correlations is a key step toward understanding cortical processing. Correlation in the local field potential (LFP) recorded from two brain areas is often characterized by computing the coherence, which is generally taken to reflect the degree of phase consistency across trials between two sites. Coherence, however, depends on two factors—phase consistency as well as amplitude covariation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 45 publications
(68 reference statements)
5
61
3
Order By: Relevance
“…1). Other studies from the same dataset have been reported previously (Ray and Maunsell 2010, 2011a, b; Srinath and Ray 2014). …”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…1). Other studies from the same dataset have been reported previously (Ray and Maunsell 2010, 2011a, b; Srinath and Ray 2014). …”
Section: Methodssupporting
confidence: 53%
“…We recorded spike and LFP signals from two male rhesus monkeys using a 10 × 10 array (Blackrock Microsystems) implanted in the V1, while they attended to a Gabor stimulus presented in the opposite hemifield of the RFs of the recorded sites and performed an orientation-change detection task [same task as used in previous studies: Ray and Maunsell (2010, 2011a); Srinath and Ray (2014); see materials and methods for details]. To estimate the spatial spread, we first estimated the RF sizes by flashing a small Gabor stimulus in a random sequence at 81 ( Monkey 1 , 9 × 9 rectangular grid spanning 2 × 2° of visual space) or 121 ( Monkey 2 , 11 × 11 grid spanning 3 × 3° of visual space) locations spanning all of the RFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While principal cells in the superficial layers of neocortex are more electrotonically compact (Zador et al, 1995), which could perhaps enable cortical circuits to more effectively employ gamma synchronization as a mechanism for selective interregional communication (Singer, 1993; Fries, 2005), this hypothesis remains hotly debated (Shadlen and Movshon, 1999; Kopell et al, 2000; Fries, 2009; Ray and Maunsell, 2010; Fell and Axmacher, 2011; Bosman et al, 2012; Akam and Kullmann, 2012; Jia et al, 2013; Srinath and Ray, 2014). In our analysis, LFP-spike coupling between CA1 units and CA3 or EC3 LFP was mostly attributable to phase-locking of interneurons (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Another spurious source of gamma coherence is amplitude covariations between signals in the same frequency band 65 . Given that power increases at gamma frequencies can also be brought about by both spiking activity and nonoscillatory transient events 66 , this is another artificial source of increased gamma coherence.…”
Section: Potential Artifactual Sources Of High-frequency Lfp Coherencementioning
confidence: 99%